The concept of ḍarūrah (necessity) in comparative fiqh - Sanusi Shamzuri, Khalish Zufayri; Mohd Zamashary, Muhammad Hariz; Mohd Amin, Muhammad Amir Azfar; Kamanedin, Kamarulhariz Akmal (2025)
In Islamic jurisprudence (fiqh), the idea of ḍarūrah (necessity) holds a prominent position as a principle that permits exceptions to conventional legal rulings in situations involving severe hardship or injury. In situations where strict application of the law would cause harm, injustice, or the failure to protect fundamental values like life, religion, intellect, lineage, and property, ḍarūrah acts as a legal mechanism to preserve essential human interests. It is rooted in the higher objectives of Islamic law (maqāṣid al-sharī‘ah). The major schools of Islamic thought Hanafi, Maliki, Shafi‘i, and Hanbali all generally agree that "necessities permit the prohibited" (al-ḍarūrāt tubīḥ al-maḥẓūrāt). However, there are significant differences in how each school defines, interprets, and practically applies the doctrine of ḍarūrah. Each school's methodological approach to legal sources, especially in the application of qiyās (analogy), istihsān (jurisprudential choice), and maslahah (public interest), has an impact on these variances. Through a comparative analysis, this project seeks to understand and apply the notion of ḍarūrah in the context of the four Sunni schools of jurisprudence. The study will provide a clearer understanding of the adaptability and flexibility of Islamic law in resolving human misery while upholding its fundamental goals by showing both the similarities and differences.